Factores de riesgo para la predicción de eventos adversos de medicamentos relacionados con la hospitalización - de Carvalho Mastroianni, Patricia [UNESP]; Varallo, Fabiana Rossi [UNESP] (Universidad de Antioquia, 2015)
The prevalence of hospital admissions because of possible adverse drug events (ADEs) vary from 0.56% to 54.5% in Brazil. In addition, nearly 43% of inpatients may develop adverse drug reactions (ADRs) during their hospital stays. Clinical outcomes arising from drug-related problems are almost never identified by health professionals because the signs and symptoms are nonspecific and may mimic pathologies.
Risk factors for early prediction of adverse drug events related to hospitalizations
Keywords: Drug-related effects and adverse reactions; Hosptialization; Pharmacovigilance